'Freedom footprints: the Barbados story' – a slavery heritage trail. Issue 5 (20th October 2017) - Best, Mechelle N.
ABSTRACT: Freedom Footprints: The Barbados Story is a heritage trail created around six slavery landmarks. The trail is an outcome of Barbados' Slave Route Signage Project, implemented by the Ministry of Tourism with the aim of identifying sites of memory linked to the Transatlantic Slave Trade and slavery, researching them and installing interpretive signage. Freedom Footprints was piloted in 2011 with much fanfare and sold-out tours. However despite significant publicity prior to and during the pilot, the voices touting the trail as an outstanding heritage tourism attraction have all but fallen silent. The reasons for this silence are unknown. A case study on Freedom Footprints was developed using a combination of stakeholder interviews, observations, analysis of media reports and archival research, among others. Indications are that the trail has potential to attract both the local and tourist market. However appropriate marketing strategies must be implemented for the trail to achieve desired outcomes.